Notary's Responsibilities for Mixed Marriage Agreements Where the Minutes of the Deed Are Not Signed by a Sworn Translator - Aristanti, Desti Yudi; Ali, Moh; Rachmad S, Iwan (CV. Rayyan Dwi Bharata, 2024)
Making a marriage agreement deed made by a Notary there are several problems that arise in the community, namely the minutes of the deed that are not signed by a sworn translator. Thus, the marriage agreement deed can be degraded into an underhand deed. The involvement and position of the sworn translator in translating a deed is as a witness, so in the provisions of UUJN Article 44 paragraph (3) the sworn translator is obliged to sign the deed, so it is the responsibility of the Notary to be more careful and careful in making a deed so that the deed is not degraded into an underhand deed which will harm the confronters in the evidentiary power of the deed. The research focus in this thesis is: First, to find the responsibility of the Notary on the mixed marriage agreement whose deed minutes are not signed by the sworn translator, Second, to find the legal consequences of the mixed marriage agreement whose deed minutes are not signed by the sworn translator, Third, to find the future arrangements on the marriage agreement made by mixed couples. This research is a normative juridical research. The approaches used are the statutory approach, used to examine the legal rules relating to the notary's responsibility for marriage agreements whose deed minutes are not signed by a sworn translator; the conceptual approach used to examine related legal certainty to the face related to the deed minutes that are not signed by a sworn translator, and the case approach to obtain legal views in order to examine and hope to reveal the issues raised in this research. First, the Notary may be subject to civil sanctions in the form of reimbursement of costs, compensation and interest for the degradation of the deed he made. Second, the legal consequences if the sworn translator does not sign the deed minutes are null and void because the sworn translator has almost the same position as the witness in the deed because the sworn translator participates in the deed making process, namely during the reading, translation or explanation of the deed and signs the deed as a formal requirement for the validity of the notarial deed. Third, the future regulation of marriage agreements made by mixed marriages by requiring the perpetrators of mixed marriages to make marriage agreements with the aim of minimizing problems that will occur in the future so that with the existence of a marriage agreement our rights are protected. Based on the results of this study, there are suggestions given, namely: First, for the legislators to make changes to the UUJN, especially regarding sanctions for notaries who are negligent in carrying out their duties in making authentic deeds, so that as a result of such negligence the deed is degraded to an underhand deed, the confronters can sue the Notary for compensation, costs and interest on the basis that the deed is degraded. The UUJN should regulate in more detail the sanctions for Notaries who are negligent in carrying out their duties. Second, to the Notary, the Notary should be more careful and thorough in making the authentic deed so that the deed will not be null and void due to contradiction with the law or the deed will be degraded into an underhand deed. Third, to the Sworn Translator, the Sworn Translator should read and explain the contents of the deed to the confrontants so that the confrontants better understand the contents of the deed. Fourth, to the perpetrators of mixed marriages, the perpetrators of mixed marriages must be given legal direction regarding the importance of marriage agreements so that all perpetrators of mixed marriages can make marriage agreements if something goes wrong, they are still protected by their rights by the existence of the marriage agreement, thus making the parties more legally secure.